Impact of Stock Split on Stock Return in Companies Listed on the India Stock Exchange - Ahmed Ahmed A. Mahmood; Estabraq Mahmood Jarallah; Mohanad Ghali Ghdhaib (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
The aim of this research is to evaluate the impact of a company's announcement, which in this case is a stock split, on the return of a company's stock listed on the Indian stock market. basing on this, the extent and significance of the effect is measured and examined through parametric and non-parametric tests. due to the aim of the paper is to test if the stock split will have a positive influence on the stock price around the implementation of the policy, we use the event study method and set regression model. In order to test the effect of the strategy, we picked estimation period and event period from each stock, and conduct regression analysis respectively. As suggested by the cumulative average AR value, the precision weighted CAAR and the ABHAR, the results imply that during the short window event of pre- and post-10 days of stock splits, the selected company have witnessed significant ARs so we reject H0 and accept H1, which suggests the presence of ARs within the event window. Similarly, other tests such as Patellz, Cross-sectional Test-t, Generalized Signz, Std. Cross-sectional Testz and Adjusted Patellz also suggest to reject H0 stating that there are ARs during the study window of the stocks splits. However, these findings are based on the 10-days event and 90-days estimation windows used for analysis and impact of the stocks splits on the stock returns of the selected company.